PENGEMBANGAN KAWASAN WONOREJO MENJADI OBYEK WISATA “TIRTA AGRO FOREST WISATA” GUNA OPTIMALISASI PEMANFAATAN WADUK BAJULMATI DI KABUPATEN SITUBONDO DAN BANYUWANGI - Yohanes Nangameka (INTEGRITAS : Jurnal Pengabdian, 2017)
Wonorejo area is located at the east end of Situbondo Regency bordering with Banyuwangi Regency which has great potential in the field of tourism. There are three potentials that are quite prominent, they are the potential of water tourism, agro tourism and forest tourism. However, these three potentials are not yet fully utilized. With the operation of the Bajulmati reservoir, it will increase all of its potentials, making it more attractive for tourism development. The potentials of tourism in this region include: 1). Food agriculture and horticulture; 2). Plantation area; 3). Forest area, 4). Aquatic area, and 5). Sea area. The development of these areas into a tourist area still faces problems, such as: 1). Differet views that have not been unified to see that the attractions of Wonorejo region can be used as Tourism Object "Tirta Agro Forest Tour"; 2). utilization of Baluran national park to be the mainstay attractions is not optimized yet; 3). Unorganized facilities and infrastructures between adjacent tourism objects become the mainstay of tourism; and 4). The readiness of human resources has not paid attention to the tourism sector. The design of Wonorejo area development becomes the area: "Tirta Agro Forest Wisata" will transform this area into a tourism area, utilizing the potential of water and sea, the potential of food agriculture and horticulture and the potential of natural resources of the forest. The logging stage of this area consists of: Phase I: identification phase of tourism potential and Phase II: Development phase with social engineering at the point of tourism development. Development point for the entire Wonorejo region as many as 18 points of tourism. So the targets achieved in the development of this region, become feasible as the area of "Tirta Agro Forest Tours".